THE PRACTICAL CHALLENGES IN LEARNING/TEACHING WRITING OF UNIVERSITY STUDENTS - Yusupova Mavluda Anvarbek kizi (XALQARO ILMIY-AMALIY ANJUMAN "TA’LIM MAYDONI TENDENSIYALARI: KOMPETENTSIYALAR, INNOVATSIYALAR VA TEXNOLOGIYALAR", 2025)
This thesis describes the difficulties faced by students and teachers in the process of mastering the written and spoken activity, which is a productive skill in English language teaching/learning. Its main purpose is to characterize the problems observed by teachers as difficulties in effective language acquisition by learners.